Face and Voice as Social Stimuli Enhance Differential Physiological Responding in a Concealed Information Test - Ambach, Wolfgang; Assmann, Birthe; Krieg, Bennet; Vaitl, Dieter (Frontiers in Psychology, 2012)
Attentional, intentional, and motivational factors are known to influence the physiological responses in a Concealed Information Test (CIT). Although concealing information is essentially a social action closely related to motivation, CIT studies typically rely on testing participants in an environment lacking of social stimuli: Subjects interact with a computer while sitting alone in an experimental room. To address this gap, we examined the influence of social stimuli on the physiological responses in a CIT. Seventy-one participants underwent a mock-crime experiment with a modified CIT. In a between-subjects design, subjects were either questioned acoustically by a pre-recorded male voice presented together with a virtual male experimenter’s uniform face or by a text field on the screen, which displayed the question devoid of face and voice. Electrodermal activity (EDA), respiration line length (RLL), phasic heart rate (pHR), and finger pulse waveform length (FPWL) were registered. The Psychopathic Personality Inventory - Revised (PPI-R) was administered in addition. The differential responses of RLL, pHR, and FPWL to probe vs. irrelevant items were greater in the condition with social stimuli than in the text condition; interestingly, the differential responses of EDA did not differ between conditions. No modulatory influence of the PPI-R sum or subscale scores was found. The results emphasize the relevance of social aspects in the process of concealing information and in its detection. Attentional demands as well as the participants’ motivation to avoid detection might be the important links between social stimuli and physiological responses in the CIT.